Effect of pioglitazone on metabolic features in endotoxemia model in obese diabetic db/db mice: 吡格列酮对肥胖的糖尿病db/db小鼠内毒素血症模型代谢特征的影响. (17th August 2016) - Sharma, Manoranjan; Mohapatra, Jogeswar; Malik, Umar; Nagar, Jignesh; Chatterjee, Abhijit; Ramachandran, Balaraman; Jain, Mukul R.
Abstract: Background: Infectious diseases are more frequent in diabetic patients, leading to increased morbidity and mortality. Endotoxemia affects glucose metabolism and lipolytic capacity. The aims of the present study were to determine whether endotoxemia exacerbates metabolic features (adipose inflammation, adipogenesis, and insulin resistance [IR]) in an animal model of diabetes (i.e. db/db mice) after acute infection and the effects of pioglitazone. Methods: Female db/db mice treated with pioglitazone (3 and 30 mg/kg, p.o.) for 14 days were challenged with lipopolysaccharide (LPS; 200 μg/kg), followed by an oral glucose tolerance test (OGTT). Quantitative real‐time polymerase chain reaction (PCR) was used to evaluate the expression of genes in white adipose tissue (WAT) involved in: (i) adipogenesis (lipoprotein lipase [ Lpl ], fatty acid binding protein‐4 [ Ap2 ] and adiponectin [ Adipoq ]); (ii) insulin signaling (peroxisome proliferator‐activated receptor gamma [ Pparg ], suppressor of cytokine signaling 3 [ Socs3 ], solute carrier family 2 [facilitated glucose transporter], member 4 [ Slc2a4 ]); and (iii) inflammation (tumor necrosis factor [ Tnf ], interleukin‐6 [ Il6 ], monocyte chemoattractant protein‐1 [ Ccl2 ], cyclo‐oxygenase‐2 [prostaglandin‐endoperoxide synthase 2; Ptgs2 ]). Results: Experimental endotoxemia downregulated mRNA expression of Pparg, Slc2a4, Adipoq, Lpl, and Ap2, which coincided with upregulation of Il6, Tnf, Ccl2, Ptgs2, and Socs3 expression. Pioglitazone dose‐dependently decreased Tnf, Il6, Ccl2, Ptgs2, and Socs3 expression in WAT, in association with upregulation of Lpl, Ap2, Slc2a4, and Adipoq expression, indicating improvement in endotoxin‐induced IR. Conclusions: The findings suggest that LPS challenge exacerbates IR in db/db mice by altering the expression of genes in WAT involved in adipogenesis and inflammation, which is effectively controlled by pioglitazone treatment. Highlights: Lipopolysaccharide‐induced endotoxemia exacerbates adipose inflammation and dysregulated adipogenesis in diabetic mice, further worsening IR; pioglitazone treatment ameliorates these effects. Pioglitazone may be a potential therapeutic agent for improving metabolic syndrome in patients with infection.